Chemical composition of cork, phloem and xylem of Quercus suber L. from different provenances - Costa, Ricardo Alexandre Rodrigues (2019)
Mestrado em Engenharia Florestal e dos recursos Naturais - Instituto Superior de Agronomia / UL